Catheter ablation of atrial fibrillation in patients with heart failure with preserved ejection fraction: a systematic review and meta-analysis. (25th November 2020) - Aldaas, O.M; Lupercio, F; Malladi, C.L; Mylavarapu, P.S; Darden, D; Han, F; Hoffmayer, K.S; Krummen, D; Ho, G; Raissi, F; Feld, G.K; Hsu, J.C
Abstract: Background: Catheter ablation improves clinical outcomes in symptomatic atrial fibrillation (AF) patients with heart failure (HF) with reduced ejection fraction (HFrEF). However, the role of catheter ablation in HF patients with a preserved ejection fraction (HFpEF) is less clear. Purpose: To determine the efficacy of catheter ablation of AF in patients with HFpEF relative to those with HFrEF. Methods: We performed an extensive literature search and systematic review of studies that compared AF recurrence at one year after catheter ablation of AF in patients with HFpEF versus those with HFrEF. Risk ratio (RR) 95% confidence intervals were measured using the Mantel-Haenszel method for dichotomous variables, where a RR<1.0 favors the HFpEF group. Results: Four studies with a total of 563 patients were included, of which 312 had HFpEF and 251 had HFrEF. All patients included were undergoing first time catheter ablation of AF. Patients with HFpEF experienced similar recurrence of AF one year after ablation on or off antiarrhythmic drugs compared to those with HFrEF (RR 0.87; 95% CI 0.69–1.10, p=0.24), as shown in Figure 1. Recurrence of AF was assessed with electrocardiography, Holter monitoring, and/or event monitoring at scheduled follow-up visits and final follow-up. Conclusion: Based on the results of this meta-analysis, catheter ablation of AF in patients with HFpEF appears as efficacious in maintaining sinus rhythm as in those with HFrEF. Funding Acknowledgement: Type of funding source: None